DAYA HAMBAT FRAKSINASI EKSTRAK SEMBUNG DELAN (SPHAERANTUS INDICUS L) TERHADAP BAKTERI ESCHERICIA COLI DAN STAPHYLOCOCCUS AUREUS - GEDE DARMAYASA, IDA BAGUS (2008)
Keywords: Fractination; Sembung Delan; Eschericia coli and Staphylococus aureus.

(untitled) (Jurnal Biologi Udayana, 2008)
A research entitled "Inhibitid activity of plant fractination extract of Sembung Delan (Sphaeranthus indicus L.) to Eschericia coli and Staphylococus aureus bacterial was carried aut to find the active of plant extract that responsible for bactericidal agent. This research used absorbance disc method to determine inhibitid fractionation extratc of Sembung Delan to growth of Eschericia coli and Staphylococus aureus bacterial. Results of this study showed that the crude extract of Sembung Delan inhibited the growth of Eschericia coli and Staphylococus aureus on Muller- Hinton medium, indicated by the formation of inhibition zone around the disc loaded with plant extract at concentration of 10,000 ppm, 20,000 ppm, 30,000 ppm, 40,000 ppm, and 50,000 ppm, with diamtre of 10mm, llmm, 12mm, 13mm and 16 mm respectively to S. aureus, forE. coli crude extract at concentration of 10,000 ppm, 20,000 ppm, 30,000 ppm, 40,000 ppm, and 50,000 ppm using diametre each of 12 mm, 13 mm, 15 mm, 17 mm and 19 mm respectively . From 17 fractions obtained from fractionation, fraction No. Vm (eluted with ethyl acetate:hexan) with Rf value of 0,9 ; 0,8 ; 0,7 ; 0,68 ; and 0,62, fraction No. DC (eluted with etihil acetate : hexan) with Rf value of : 0,98, ; 0,94 ; and 0,82, fraction No. XV (eluted with ethyl acetate 100%) Rf value of : 0.03; 0.23; 0.35 and fraction No. XVI (eluted with ethyl acetate 100%) with Rf value of: 0.03; 0.14; 0.17; 0.21, effectivity inhibited the growth of test bacterial.